PERBEDAAN TINGKAT KECEMASAN PASIEN HIPERTENSI YANG MENDAPATKAN PROGRAM PENGOBATAN SATU JENIS OBAT DENGAN YANG MENDAPATKAN LEBIH DARI SATU JENIS OBAT ANTIHIPERTENSI DI PUSKESMAS JETIS YOGYAKARTA - isnanto, Isnanto; Shello, Pentanis Beshi Kronica (Jurnal Kesehatan, 2017)
Background: The incidence of hypertension is expected to increase despite followed by developing prevention, detection, and medical treatment. Antihypertension medical treatment with a single close or long term combination for a life time causes the possibility of unidentified anxiety. Therefore it can reduce the expected medical treatment result. Objective: To determine the differences in anxiety level between hypertension patients who are given medical treatment program with one type of medicine and more than one type of antihypertension medicine at Puskesmas Jetis Yogyakarta in 2016. Method: Researcher used comparative analytic by using cross sectional approach. The data was taken from total 135 population and 40 patients which were diveded into two groups. Researcher used simple random sampling technique. Researcher used Beck anxiety inventory (BAI) to detect anxiety levels as the instrument and to analyse the data used Mann - Whitney. Result: Z count -2,892, sig or p value 0,004 < 0,05 of error rate. Conclusion: There are differences in anxiety level between hypertension patients who are given medical treatment program with one type of medicine and more than one type of antihypertension medicine. Suggestions: Other researchers can examine the differences in anxiety level between hypertension patient’s who are given medical treatment program antihypertension medicine with the level of knowledge about the effect of antihypertension medicine. Keywords: Anxiety Level – Hypertension – Antyhipertension